A negative ion releasing material

CN121319742BActive Publication Date: 2026-10-27GUANGZHOU BOAO SPORTS FACILITIES ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511695498.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-19
Publication Date
2026-10-27
Estimated Expiration
2045-11-19

AI Technical Summary

Technical Problem

在电镀、化工等行业中使用的环氧树脂地坪漆对其耐腐蚀性能有着较高的要求,由于地坪漆的施工工艺,往往修补的供需繁琐,而且修补后效果无法与原地坪漆一致,导致色差或接口不平、开裂等情况

Benefits of technology

本发明将羧基化纤维素纳米纤维与氨基化石墨烯进行键合组装,同时还用碳化硅纳米线进行修饰制备了改性石墨烯,改性石墨烯添加到地负离子释放材料中形成地坪漆,提升了漆膜的韧性、抗冲击力。本发明的制备工艺简单,安全环保,电气石粉的添加可以赋予地坪漆一定的产生负离子的能力,提供杀菌、净化、养生等功效具有较好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of negative ion release materials, the negative ion release materials include, 90~120 parts water-based epoxy resin, 30~60 parts curing agent, 20~30 parts color filler, 5~15 parts tourmaline powder, 5~10 parts modified graphene, 1~2 parts leveling agent, 0.5~1 parts defoaming agent, 0.5~1 parts dispersing agent, 10~30 parts water by mass parts;The modified graphene is obtained by modifying silicon carbide nanowire, carboxylated cellulose nanofiber on the surface of aminated graphene.The application is bonded and assembled to carboxylated cellulose nanofiber and aminated graphene, and is also modified by silicon carbide nanowire to prepare modified graphene, which is added to the floor negative ion release material to form floor paint, and the toughness and impact resistance of the paint film are improved.The preparation process of the application is simple, safe and environmentally friendly.The addition of tourmaline powder can give the floor paint certain ability to generate negative ions, provide sterilization, purification, health care and other effects, and has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of floor coating technology, and in particular to negative ion releasing materials. Background Technology

[0002] Floor paint is a type of coating specifically designed for floor application, typically used on indoor or outdoor concrete or cement floors. Its main functions are to protect the floor, enhance its wear resistance, prevent pollution and corrosion, and also improve its aesthetics. There are many types of floor paint, with epoxy floor paint being the most widely used and diverse. Epoxy resin floor paints used in industries such as electroplating and chemicals have high requirements for corrosion resistance. Due to the complex application process of floor paint, repairs are often cumbersome, and the repaired finish may not match the original, leading to color differences, uneven joints, cracking, and other issues. Therefore, floor paints need a relatively long service life, meaning epoxy resin floor paints need to have higher wear resistance and corrosion resistance.

[0003] Several existing technologies have provided epoxy resin floor coatings with excellent performance. For example, CN114350229A discloses a graphene-modified epoxy resin floor coating and its preparation method. The method involves an amidation reaction between trimethylamine and acylchloromethylated graphene to obtain m-phenylenediamine-modified graphene, an esterification reaction between polyethylene glycol 800 and p-hydroxybenzoic acid to obtain p-hydroxybenzoic acid-based polyethylene glycol, and an in-situ polymerization reaction between the p-phenylenediamine-modified graphene, m-phenylenediamine, and formaldehyde solution to obtain phenolic resin-modified graphene. The layered graphene oxide can shield numerous tiny pores, thus providing corrosion resistance. The polyethylene glycol 800 contains a large number of hydrophilic groups, effectively improving the water-based properties of the epoxy resin. The phenolic resin and graphene oxide possess excellent mechanical properties, effectively improving the mechanical properties of the epoxy resin, resulting in epoxy resin floor coatings with superior mechanical properties and excellent corrosion resistance.

[0004] Adding appropriate modifiers to the base epoxy resin can help improve the performance of epoxy resin floor coatings. Summary of the Invention

[0005] To address the technical problems existing in the prior art, this invention provides a negative ion releasing material, comprising the following raw materials in parts by mass: 90-120 parts waterborne epoxy resin, 30-60 parts curing agent, 20-30 parts pigments and fillers, 5-15 parts tourmaline powder, 5-10 parts modified graphene, 1-2 parts leveling agent, 0.5-1 part defoamer, 0.5-1 part dispersant, 10-30 parts water; The modified graphene was obtained by modifying the surface of aminated graphene with silicon carbide nanowires and carboxylated cellulose nanofibers.

[0006] A negative ion releasing material is obtained by mixing waterborne epoxy resin, pigments and fillers, modified graphene, and water, followed by adding curing agent, leveling agent, defoamer, and dispersant, and then degassing the mixture.

[0007] Tourmaline is a general term for minerals in the tourmaline group. Its chemical composition is complex; it is a cyclic silicate mineral characterized by boron content and containing aluminum, sodium, iron, magnesium, and lithium. It is also known as tourmaline or jasper. Tourmaline exhibits piezoelectric and pyroelectric properties. Due to the constant changes in air pressure and temperature, positive and negative charges separate at the ends of the tourmaline crystal, generating a potential that discharges instantaneously, ionizing the air and producing negative ions. Therefore, tourmaline can continuously and permanently generate negative ions in the air. Negative ions have bactericidal, purifying, and health-promoting effects. Adding tourmaline powder to floor coatings can endow them with the ability to generate negative ions, providing additional benefits.

[0008] Aminated graphene is formed by the amination reaction of graphene. It has a higher specific surface area and abundant functional groups, making it easier to modify than graphene.

[0009] Silicon carbide, industrially produced by high-temperature smelting of raw materials such as quartz sand, petroleum coke (or coal coke), and sawdust in an electric resistance furnace, is also known as diamond sand or refractory sand. Silicon carbide possesses stable chemical properties, high thermal conductivity, low coefficient of thermal expansion, good wear resistance, and high hardness. When used in floor coatings, it not only acts as a filler, thickener, and matte agent, but also improves the fineness, leveling properties, film hardness, and arc resistance of the coating. Currently, silicon carbide micropowder is widely used in floor coatings, with almost no reports on silicon carbide nanowires (fibers).

[0010] Cellulose nanofibers are nanoscale biomass polymers extracted from natural cellulose, possessing a longitudinal modulus of 100–130 GPa (iron: 200–220 GPa), but a density only one-sixth that of iron. Furthermore, due to their large specific surface area, high aspect ratio, and abundant functional groups, they readily interweave with matrix materials to form a network structure, further enhancing their overall mechanical properties. Carboxylated cellulose nanofibers, possessing carboxyl groups, can chemically bond with aminographene to form stable complexes.

[0011] Furthermore, the method for preparing the modified graphene includes, by weight, the following: 0.2-0.5 parts of polyethylene glycol 2000, 0.1-0.5 parts of carboxylated cellulose nanofibers, 0.2-0.8 parts of silicon carbide nanowires, 5-10 parts of aminated graphene, and 200-300 parts of water were mixed and stirred at 60-80℃ for 6-18 hours, followed by freeze drying to obtain modified graphene.

[0012] Furthermore, the silicon carbide nanowires have a diameter of less than 500 nm and a length of 50~100 μm.

[0013] Furthermore, the carboxylated cellulose nanofibers have a diameter of 4-10 nm and a length of less than 200 nm.

[0014] Furthermore, the curing agent is at least one of aliphatic amines, aromatic amines, polyamides, and acid anhydrides.

[0015] Furthermore, the pigment or filler is at least one of quartz powder, talc powder, titanium dioxide, or barium sulfate.

[0016] Furthermore, the leveling agent is a modified polyether siloxane type leveling agent.

[0017] Furthermore, the defoamer is at least one of a high-carbon alcohol defoamer and an organosilicon defoamer.

[0018] Furthermore, the dispersant is one of sodium polycarboxylate, potassium polyacrylate, and sodium polyacrylate.

[0019] This invention also provides a method for preparing the above-mentioned negative ion releasing material, including, A negative ion releasing material is obtained by mixing waterborne epoxy resin, pigments and fillers, tourmaline powder, modified graphene, and water, followed by adding curing agent, leveling agent, defoamer, and dispersant, and then degassing the mixture.

[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention involves bonding and assembling carboxylated cellulose nanofibers with aminated graphene, and further modifying the graphene with silicon carbide nanowires to prepare modified graphene. The modified graphene is then added to a negative ion-releasing material to form a floor coating, enhancing the toughness and impact resistance of the coating film. The preparation process of this invention is simple, safe, and environmentally friendly. The addition of tourmaline powder endows the floor coating with a certain ability to generate negative ions, providing bactericidal, purifying, and health-promoting effects, and has good application prospects. Detailed Implementation

[0021] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0022] Description of some of the raw materials used in the embodiments of this invention: Waterborne epoxy resin, brand name E-44, purchased from Angsen Building Materials Hebei Co., Ltd. Tourmaline powder, item number DQSF-96, mesh size 2000, purchased from Shijiazhuang Ailun Mineral Products Co., Ltd. Silicon carbide nanowires, model D500-NW, with a diameter of less than 500 nm and a length of 50~100 μm, were purchased from Guangzhou Hongwu Materials Technology Co., Ltd. Carboxylated cellulose nanofibers, catalog number PA28434, with a diameter of 4~10nm, a length of approximately 200nm, and a solid content of 6% (solvent is water), were purchased from Shanghai Bofei Meco Chemical Technology Co., Ltd. Aminographene, item number BKMK2009, purchased from Suzhou Kaifa New Material Technology Co., Ltd. Aliphatic amine curing agent, brand name 593, purchased from Wuhan Adoma New Energy Co., Ltd. Modified polyether siloxane leveling agent, model BYK-333, purchased from BYK Chemicals; Silicone defoamer, model BYK-065, purchased from BYK Chemicals; Sodium polycarboxylate, model KJH, purchased from Shandong Fushun New Material Technology Co., Ltd.

[0023] Other raw materials not mentioned are common in the field. The above content is only for the purpose of illustrating the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them themselves.

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1

[0025] A method for preparing a negative ion releasing material, comprising the following steps in parts by mass: Step 1: Weigh out 100 parts of water-based epoxy resin, 40 parts of aliphatic amine curing agent, 15 parts of 500-mesh titanium dioxide, 15 parts of 1250-mesh barium sulfate, 10 parts of tourmaline powder, 9 parts of modified graphene, 1 part of modified polyether siloxane leveling agent, 0.8 parts of organosilicon defoamer, 0.75 parts of sodium polycarboxylate, and 30 parts of water. Step 2: Mix waterborne epoxy resin, titanium dioxide, barium sulfate, tourmaline powder, modified graphene, and water at a stirring speed of 1500 rpm for 30 minutes to obtain a mixture. Step 3: Add aliphatic amine curing agent, modified polyether siloxane leveling agent, organosilicon defoamer, and sodium polycarboxylate to the mixture obtained in Step 2, stir and mix at a stirring rate of 1000 rpm for 10 min, and then degas to obtain negative ion releasing material.

[0026] The preparation method of modified graphene, in parts by mass, is as follows: 0.5 parts of polyethylene glycol 2000, 0.1 parts of carboxylated cellulose nanofibers, 0.3 parts of silicon carbide nanowires, 10 parts of aminated graphene, and 300 parts of water were mixed and reacted at 80°C with a stirring rate of 300 rpm for 12 h. The mixture was then transferred to -45°C for freeze drying to obtain modified graphene. Example 2

[0027] A method for preparing a negative ion releasing material is basically the same as in Example 1, except that the modified graphene is prepared by mixing 0.5 parts polyethylene glycol 2000, 0.3 parts carboxylated cellulose nanofibers, 0.5 parts silicon carbide nanowires, 10 parts aminated graphene, and 300 parts water at 80°C with a stirring rate of 300 rpm for 12 hours, and then transferring to -45°C for freeze drying to obtain modified graphene. Example 3

[0028] A method for preparing a negative ion releasing material is basically the same as in Example 1, except that the modified graphene is prepared by mixing 0.5 parts polyethylene glycol 2000, 0.5 parts carboxylated cellulose nanofibers, 0.8 parts silicon carbide nanowires, 10 parts aminated graphene, and 300 parts water at 80°C with a stirring rate of 300 rpm for 12 hours, and then transferring to -45°C for freeze drying to obtain modified graphene.

[0029] Comparative Example 1 The method is basically the same as in Example 2, except that the modified graphene is prepared by mixing 0.5 parts polyethylene glycol 2000, 0.8 parts carboxylated cellulose nanofibers, 10 parts aminated graphene and 300 parts water by mass, stirring at 80°C and 300 rpm for 12 h, and then transferring to -45°C for freeze drying to obtain modified graphene.

[0030] Comparative Example 2 The method is basically the same as in Example 2, except that the modified graphene is prepared by mixing 0.5 parts of polyethylene glycol 2000, 0.8 parts of silicon carbide nanowires, 10 parts of aminated graphene and 300 parts of water at 80°C with a stirring rate of 300 rpm for 12 hours, and then transferring to -45°C for freeze drying to obtain modified graphene.

[0031] Comparative Example 3 The method is basically the same as in Example 2, except that the modified graphene is prepared by mixing 0.3 parts by weight of carboxylated cellulose nanofibers, 0.5 parts by weight of silicon carbide nanowires, 10 parts by weight of aminated graphene and 300 parts by weight of water, stirring at 80°C and stirring at 300 rpm for 12 h, and then transferring to -45°C for freeze drying to obtain modified graphene.

[0032] Comparative Example 4 The method is basically the same as in Example 2, except that the modified graphene is prepared by mixing 0.5 parts polyethylene glycol 2000, 0.3 parts carboxylated cellulose nanofibers, 0.5 parts silicon carbide nanowires, 10 parts graphene, and 300 parts water at 80°C with a stirring rate of 300 rpm for 12 hours, and then transferring to -45°C for freeze drying to obtain modified graphene.

[0033] Test case The waterborne epoxy resin floor coatings of the examples and comparative examples were tested for impact resistance, compressive strength, hardness and adhesion in accordance with GB / T50589-2010 "Technical Specification for Epoxy Resin Self-Leveling Floor Engineering". The results are shown in Table 1.

[0034] Table 1 Performance test results of waterborne epoxy resin floor coating

[0035] As can be seen from the results in Table 1, compared with the comparative examples, the negative ion releasing materials prepared in Examples 1-3 of this invention exhibit better impact resistance, higher compressive strength, higher hardness, and greater adhesion when used as floor coatings. This is because graphene / aminographene exhibits poor dispersibility in aqueous epoxy resins. Carboxylated cellulose nanofibers and aminographene, in addition to hydrogen bonding, also have chemical bonds, thus exhibiting a stronger interaction. Silicon carbide nanowires have a weaker interaction with aminographene. The presence of polyethylene glycol 2000 can significantly improve the dispersibility of silicon carbide nanowires in the aminographene mixed solution. Carboxylated cellulose nanofibers can self-assemble to modify the surface of aminographene, forming a three-dimensional network-like structure, thereby enhancing the interaction between silicon carbide nanowires and aminographene, and thus improving the dispersibility and stability of modified graphene in epoxy resins.

[0036] The abrasion resistance of the waterborne epoxy resin floor coatings in the examples and comparative examples was tested according to the standard GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method", and the results are shown in Table 2.

[0037] Table 2 Abrasion resistance results Example 1 0.011 Example 2 0.010 Example 3 0.013 Comparative Example 1 0.018 Comparative Example 2 0.020 Comparative Example 3 0.023 Comparative Example 4 0.027 As can be seen from the test results in Table 2, the negative ion releasing materials prepared in Examples 1 to 3 of this invention have good wear resistance as floor coatings. In particular, the wear resistance (750g / 500r, g) of Example 2 is as low as 0.010. These results indicate that the film structure of the floor coatings prepared in these examples is more compact. This is attributed to the fact that in the presence of polyethylene glycol 2000, silicon carbide nanowires can form a stable structure with the three-dimensional network formed by the self-assembly modification of carboxylated cellulose nanofibers on the surface of aminated graphene. This compensates for the edge defects of aminated graphene and enhances its dispersibility in waterborne epoxy resin, thus significantly improving the wear resistance of the floor coating.

[0038] The epoxy resin floor coatings prepared in the embodiments and comparative examples of this invention were sprayed onto a steel plate with a thickness of 1 mm, a length of 15 mm, and a width of 10 mm using a spray gun. After curing, a 50 μm layer was formed. This layer was used as the working electrode, with a platinum electrode and a saturated calomel electrode as the counter electrode and reference electrode, respectively. The plates were connected to an electrochemical workstation. The test solution was a 3.5 wt.% NaCl solution. After the sample was stabilized under open-circuit voltage testing, the open-circuit voltage value was obtained. Then, the scanning voltage range was set to ±500 mV, the potential scan rate was 1 mV / s, and the frequency range was 10. -2 ~10 5 The corrosion current density results are shown in Table 3.

[0039] Table 3 Corrosion Current Density Results Example 1 5.62 Example 2 3.86 Example 3 6.91 Comparative Example 1 8.95 Comparative Example 2 9.14 Comparative Example 3 16.34 Comparative Example 4 21.13 As can be seen from the test results in Table 3, the paint film of the present invention has a lower corrosion current density, which indicates that it has stronger corrosion resistance.

[0040] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a negative ion releasing material, characterized in that, The steps for calculating by mass parts are as follows: Step 1: Weigh out 100 parts of water-based epoxy resin, 40 parts of aliphatic amine curing agent, 15 parts of 500-mesh titanium dioxide, 15 parts of 1250-mesh barium sulfate, 10 parts of tourmaline powder, 9 parts of modified graphene, 1 part of modified polyether siloxane leveling agent, 0.8 parts of organosilicon defoamer, 0.75 parts of sodium polycarboxylate, and 30 parts of water. Step 2: Mix waterborne epoxy resin, titanium dioxide, barium sulfate, tourmaline powder, modified graphene, and water at a stirring speed of 1500 rpm for 30 minutes to obtain a mixture. Step 3: Add aliphatic amine curing agent, modified polyether siloxane leveling agent, organosilicon defoamer, and sodium polycarboxylate to the mixture obtained in Step 2, stir and mix at a stirring rate of 1000 rpm for 10 min, and then degas to obtain negative ion releasing material. The modified graphene was prepared by mixing 0.5 parts polyethylene glycol 2000, 0.3 parts carboxylated cellulose nanofibers, 0.5 parts silicon carbide nanowires, 10 parts aminated graphene, and 300 parts water at 80°C with a stirring rate of 300 rpm for 12 h, and then freeze-drying at -45°C to obtain the modified graphene.

Citation Information

Patent Citations

  • Graphene modified epoxy resin floor paint and preparation method thereof

    CN114350229A

  • Preparation method of nano graphene negative ion coating

    CN113372792A

  • Degradable graphene conductive paste and RFID electronic tag

    CN114864135A

  • High-performance electronic paste based on graphene composite material and preparation method thereof

    CN120376215A

  • High-performance biological material based on hydroxypropyl-beta-cyclodextrin and preparation method thereof

    CN120818161A